Enhanced Reactive Blue 4 Biodegradation Performance of Newly Isolated white rot fungus Antrodia P5 by the Synergistic Effect of Herbal Extraction Residue - Yuan, Tianjie; Zhang, Shuyi; Chen, Yifei; Zhang, Ran; Chen, Letian; Ruan, Xiaoshu; Zhang, Sen; Zhang, Fang (Frontiers in Microbiology, 2021)
In this study, a white rot fungus Antrodia was newly isolated and named P5. Then its dye biodegradation ability was investigated. Our results showed that P5 could effectively degrade 1000 mg/L Reactive Blue 4 (RB4) in 24 h with 95% decolorization under shaking conditions. It could tolerate a high dye concentration of 2500 mg/L as well as 10% salt concentration and a wide range of pH values (4–9). Herbal extraction residues (HER) were screened as additional medium elements for P5 biodegradation. Following the addition of Fructus Gardeniae (FG) extraction residue, the biodegradation performance of P5 was significantly enhanced, achieving 92% decolorization in 12 h. Transcriptome analysis showed that the expression of multiple peroxidase genes was simultaneously increased: Lignin Peroxidase, Manganese Peroxidase, Laccase, and Dye Decolorization Peroxidase. The maximum increase in Lignin Peroxidase reached 10.22-fold in the presence of FG. The results of UV scanning and LC-HRMS showed that with the synergistic effect of FG, P5 could remarkably accelerate the biodegradation process of RB4 intermediates. Moreover, the fungal treatment with FG also promoted the abatement of RB4 toxicity. In sum, white rot fungus and herbal extraction residue were combined and used in the treatment of anthraquinone dye. This could be applied in practical contexts to realize an efficient and eco-friendly strategy for industrial dye wastewater treatment.